Adaptive optics correction of beam spread in biological tissues. (June 2022) - Baykal, Yahya
Highlights: Beam spread in turbulent biological tissues is examined. Piston and tilt corrections are applied to beam spread. Reduction in beam spread with piston and tilt corrections is evaluated. Piston+tilt corrected beam spread is evaluated against tissue turbulence parameters. Abstract: Beam spread in turbulent biological tissues is examined when the tissue is excited with a collimated Gaussian laser beam. Adaptive optics correction is applied to the beam spread in the form of piston only (P Only), tilt only (T Only), piston+tilt (P+T), and the reduction in the beam spread is evaluated as compared to the no adaptive optics (No AO) corrected beam spread. No AO and adaptive optics corrected beam spread are expressed for various biological tissue types, against the variations in the strength coefficient of the refractive-index fluctuations, source size, small length-scale factor of turbulence, tissue length, fractal dimension, characteristic lengths of heterogeneity and the wavelength. For the examined tissue types of liver parenchyma (mouse), intestinal epithelium (mouse), upper dermis (human) and deep dermis (mouse), No AO beam spread and the adaptive optics corrected beam spread are found to increase as the strength coefficient of the refractive-index fluctuations, tissue length, fractal dimension, the characteristic lengths of heterogeneity increase, and to decrease as the source size, small length-scale factor, wavelength increase. Reduction ratio of P+T correction is almost the same for all the evaluated cases which is 74%.